Structural dynamics of an excited donor–acceptor complex from ultrafast polarized infrared spectroscopy, molecular dynamics simulations, and quantum chemical calculations12. Issue 22 (22nd May 2019) - Rumble, Christopher A.; Vauthey, Eric
Abstract : Infrared anisotropy experiments and mixed quantum/classical computations demonstrate large scale reorientation following excitation of a donor/acceptor complex. Abstract : The structural dynamics of an electron donor/acceptor complex (DAC) consisting of benzene and tetracyanoethylene (Bz/TCNE) solvated in CH2 Cl2 have been investigated using ultrafast spectroscopy and mixed quantum/classical computer simulations. Population dynamics from visible and infrared transient absorption (TRIR) spectroscopy point to complex sub-10 ps dynamics followed by charge recombination on a 55–60 ps timescale. Structural dynamics involving large-scale reorganization of Bz˙ + /TCNE˙ − radical ion pairs are revealed using TRIR anisotropy measurements. A computational study combining quantum chemical calculations and classical molecular dynamics simulations was able to reproduce the experimental electronic absorption lineshape and TRIR anisotropy dynamics, allowing for a detailed investigation of the pair conformational dynamics. Contrary to the static single structure typically assumed in descriptions of DACs, we find that neither the ground nor excited state can be described using a single, well-defined species. Instead, the pair undergoes a rearrangement from disordered π-stacks to edge-to-face T-shaped structures following excitation. Translational diffusion of the radical ion pairs following excitation was found to be heterogeneous and dependent on both pair separation and orientation coordinates. Given the sensitivity of charge-transfer reactions to the arrangement of donor/acceptor pairs, the structural heterogeneity and corresponding dynamics demonstrated herein must be taken into account in future modeling of charge recombination processes in DACs.